Ecophysiological responses of Themeda triandra Forsk. and other Southern African C₄ grass species to increases in atmospheric CO₂ concentrations - Wand, Stephanie Juliane Editha (Department of Biological Sciences, 2024)
This study was undertaken to investigate the potential effects of rising atmospheric carbon dioxide (C02) concentrations on southern African C4 grass species, with respect to carbon assimilation and allocation, growth, and morphological development. Altered CO2-responsiveness with simultaneous exposure to other environmental influences was also assessed in order to estimate the impacts of elevated CO2 on the future distribution and productivity of grasslands in southern Africa. The initial hypothesis was based on established theory and current perceptions, which predict no significant photosynthetic or growth responses to elevated CO2 in C4 grasses. Three different approaches were employed to test a range of questions: ., A quantitative literature review (meta-analysis) was undertaken of physiological and growth responses to elevated CO2 of wild C3 and C4 grass species worldwide, in order to test the current perception of non-responsiveness in C4 species . ., Selected representative southern African C4 grass species were grown from seed or from small tufts for periods of at least four months in open-top chambers in a greenhouse under either ambient (360 Ilmol mor1 ) or elevated (650-700 Ilmol mor1 ) CO2 concentration. Both inter- and intra-specific variability in the CO2-response were studied, under different seasonal temperature regimes. The CO2 treatments were also combined with defoliation and increased ultraviolet-B (UV -B) radiation treatments, and comparisons were made with the CO2- responsiveness of woody grassland invaders, in order to examine the potentially moderating influence of other climatic and biological factors on C4 responses. • Photosynthetic responses to elevated CO2 of selected C4 and C3 grass species were determined under natural conditions in a field experiment situated in a C4-dominated grassland in KwazululNatal. Potential seasonal shifts in CO2-responsiveness were investigated over the course of a year, to determine possible linkages with plant phenology.